2013
DOI: 10.5539/jedp.v3n2p138
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Exhaustion in Graduate Students: The Role of Engagement, Self-Efficacy and Social Support

Abstract: Graduate students, particularly those based in research intensive universities are susceptible to exhaustion. The study utilized a quantitative approach to test the impact of student engagement, self-efficacy, and social support on college students' emotional exhaustion. A hierarchical regression approach was used for analysis. Findings demonstrated that students who were engaged, and self -efficacious were less exhausted from their studies. Social support especially from advisors was important in helping stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 47 publications
3
28
0
21
Order By: Relevance
“…Moreover, doctoral students who had considered interrupting their studies were more stressed and suffered more from negative feelings such as anxiety and exhaustion than their peers who had not considered such a course of action . On the other hand, it appears that social support from supervisors helped to ease emotional exhaustion (Rigg, Day, & Adler, 2013). Likewise, it has been found that a high degree of integration into the researcher community increases the likelihood of timely completion of the doctoral degree (Hermann et al, 2014;Jairam & Kahl, 2012;Wao & Onwuegbuzie, 2011).…”
Section: Burnoutmentioning
confidence: 99%
“…Moreover, doctoral students who had considered interrupting their studies were more stressed and suffered more from negative feelings such as anxiety and exhaustion than their peers who had not considered such a course of action . On the other hand, it appears that social support from supervisors helped to ease emotional exhaustion (Rigg, Day, & Adler, 2013). Likewise, it has been found that a high degree of integration into the researcher community increases the likelihood of timely completion of the doctoral degree (Hermann et al, 2014;Jairam & Kahl, 2012;Wao & Onwuegbuzie, 2011).…”
Section: Burnoutmentioning
confidence: 99%
“…Emotional exhaustion also appears to influence doctoral students' withdrawal intentions (Rigg et al, 2013). A recent study of Finnish doctoral students found that those who experienced higher anxiety and emotional exhaustion demonstrated lower interest in their studies and considered withdrawing from their program (Pyhältö et al, 2012).…”
Section: Emotional Exhaustion and Attritionmentioning
confidence: 99%
“…Pyhältö et al (2012) analyzed factors that contribute to doctoral student achievement, and suggested that the context of a doctoral student's learning environment can either promote well-being and success, or can result in dysfunctional emotions and withdrawal. While a few recent studies have examined doctoral student well-being (e.g., Juniper, Walsh, Richardson, & Morley, 2012;Rigg, Day, & Adler, 2013;Stubb et al, 2011), our understanding of the factors that affect doctoral student well-being and persistence in academia remains incomplete. Consequently, the purpose of this study is to gain a better understanding of factors that affect doctoral students' emotional well-being and influence their intentions to leave academia.…”
Section: Doctoral Student Persistencementioning
confidence: 99%
“…Doctoral supervisors can provide invaluable direction for students such as resources, knowledge in the discipline, study structure, research skill development, regular feedback, and publishing opportunities. Although perceptions among doctoral students and their supervisors differ regarding the role of the supervisor (Orellana et al, 2016), extant research shows that adequate supervision reduces attrition (Pyhältö, Vekkaila, & Keskinen, 2015) and emotional exhaustion (Rigg, Day, & Adler, 2013), and doctoral students benefit when the supervision varies (Cornér, Löfström, & Pyhältö, 2017). Although doctoral students should transform from course-takers into autonomous researchers, supervisors can facilitate the development of independent scholars by offering their expertise and guidance.…”
Section: Online Doctoral Studentsmentioning
confidence: 99%